Original paper Activity of cathepsin D and α1-antitrypsin in blood of men with malignant melanoma - Kuźniewski, Rafał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction : The aetiopathology of melanoma is (like in other cancers) a result of environmental factors and genetic predispositions. One of the most important environmental factors which has an influence on melanoma aetiology is exposure to UV radiation. Aim : To estimate the activity of selected parameters in melanoma diagnosis. Material and methods: In serum of 25 men with melanoma, activity of cathepsin D and α1-antitrypsin (important inhibitors of protease) was estimated. It was a heterogeneous group, because some men were classified according to Clark’s classification, and other men were classified by Breslow’s classification. Three months after resection of the lesion, only 13 men came back for the next tests. Results: Activity of α1-antitrypsin in patients before and after removing the affected tissue was similar and related to the control value (0.78 mg of trypsin). Medium activity of cathepsin D in the control group was about 11.88 nM. Activity in patients before surgery was lower: 8.94 nM. After removing the tumour, this activity was 9.31 nM. Conclusions : It can be supposed that the proteolytic-antiproteolytic balance was disturbed in persons with melanoma, because the activity of cathepsin D in serum of these people was lower than in healthy people, but the activity of α1-antitrypsin was not changed.